Commentary: Treatment Considerations for Patients With Epidermal Growth Factor Receptor‐Mutated Non‐Small Cell Lung Cancer Brain Metastases in the Era of Tyrosine Kinase Inhibitors. Issue 1 (January 2018) - Vaca, Silvia Daniela; Connolly, Ian David; Ho, Clement; Neal, Joel; Gephart, Melanie Hayden
Abstract : N/A: Brain metastasis is a serious complication of non‐small cell lung cancer (NSCLC) affecting up to 40% of NSCLC patients. A subset of NSCLC tumors has mutations in the epidermal growth factor receptor (EGFR) gene, and determination of tumor EGFR mutation status is essential in guiding treatment decisions, as it directly affects the treatment approach. Patients with EGFR‐mutated NSCLC have a higher cumulative incidence of brain metastases, and are especially sensitive to EGFR tyrosine kinase inhibitors (TKIs). Patients with newly diagnosed EGFR‐mutated lung cancer presenting to a neurosurgeon with a new diagnosis of brain metastases now have a variety of treatment options available, including whole brain radiation therapy, stereotactic radiosurgery, surgical resection, chemotherapy, and targeted therapeutics such as the EGFR TKIs. In this review, we discuss the impact of EGFR mutation status on brain and leptomeningeal metastasis treatment considerations. Additionally, we present clinical cases of patients treated with EGFR TKIs alone and in combination with other therapies to highlight treatment alternatives.